Godsdiensvryheid in die lig van Artikel 36 NGB - Coetzee, CFC (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Religious freedom is a matter of great importance and concern for churches in the new South Africa. Furthermore, there is no consensus amongst theologians on what exactly the role of the government should be in this regard. In this article the relationship between church and government is discussed from a theological perspective with special reference to Article 36 of the Belgic Confession.